Pengaruh Customer Relationship Management (CRM) terhadap Loyalitas Pelanggan Dengan Kepuasan Kerja sebagai Variabel Moderat - Titin Trimintarsih (REVITALISASI : Jurnal Ilmu Manajemen, 2023)
Relationships with customers is more important than setting sales goals. Customer Relationship Management is one way to satisfy and retain loyal customers, and this method will be applied in research for businessman in Kampung Tahu Kota Kediri. The reason for choosing a location in Kampung Tahu that there are approximately 30 more businessman who have the same product, with the same location, so that the level of competition in Kampung Tahu is very tight and must avoid customer grabs, negative impacts. This research focused on the tofu industry house "Sidodadi" which is also located in the tofu village, by taking 50 samples of customers with 20 questionnaire questions. Using Descriptive quantitative methods with the Application of CRM programs to Customer Loyalty and Job Satisfaction as a Moderate Variable. Calculations using SPSS theory produce an analysis of the R2 squere value of 0.562. CRM was able to explain loyalty by 56.2% and the remaining 43.8% was explained by other variables not studied in this research. As known that the higher the CRM, the higher the customer loyalty. The conclusions of research that the better or more attractive the CRM program applied to the tofu industry, the loyalty from customers will increase. Keywords : CRM, satisfied, loyalty, moderating